2010
DOI: 10.1007/s00192-010-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of intravesical hyaluronan therapy in bladder pain syndrome/interstitial cystitis

Abstract: Besides a high rate of acute symptom remission, intravesical hyaluronan also shows long-term efficacy in a considerable number of BPS/IC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 17 publications
4
57
2
1
Order By: Relevance
“…The largest ES in all CT studies was observed for HMW-HA in the study by Shao et al (Fig. 2) [34], with similar findings in two UCT studies with HMW-HA [16,40] by a superior Bd^for average VAS difference. Closest to this VAS reduction were the results obtained using 300 mg of intravesical PPS [47].…”
Section: Evaluation Of Efficacysupporting
confidence: 71%
See 3 more Smart Citations
“…The largest ES in all CT studies was observed for HMW-HA in the study by Shao et al (Fig. 2) [34], with similar findings in two UCT studies with HMW-HA [16,40] by a superior Bd^for average VAS difference. Closest to this VAS reduction were the results obtained using 300 mg of intravesical PPS [47].…”
Section: Evaluation Of Efficacysupporting
confidence: 71%
“…The final set of 19 articles on intravesical BPS/IC therapy was further qualitatively and quantitatively analysed: 5 studies were prospective controlled trials [34][35][36][37][38], 1 compared different intravesical products [39], 1 paper was designed as a retrospective study [40], and another 1 compared two different regimens of the same product [41]. The rest of the trials were classified as uncontrolled clinical studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Chondroitin sulfate (Uracyst, Gepan) -A meta-analysis by Thakkinstian et al has shown a global response rate of 43% in the chondroitin sulfate group when compared to placebo. 10 Pentosan polysulfate (PPS) -Most effective when combined with oral PPS; however, not readily available in the UK.…”
Section: Bladder Instillationsmentioning
confidence: 99%